PENGELOLAAN SISTEM INFORMASI PENDIDIKAN ISLAM: Management of Islamic Education Information Systems - Muhammad Naelul Mubarok; Andini Fajri (Ikatan Sarjana Al-Qur'an Indonesia (ISQI), 2024)
Management of the Islamic Education Information System is an important aspect in supporting educational operations, management and planning. This system is a combination of human resources and information technology to provide accurate and structured information. The aim of Islamic Education Information System Management is to improve the efficiency, effectiveness and quality of Islamic education through data and information management. By using research in the form of a literature review, the author carried out a serious review of academic texts in the form of journals, books and articles. Results of research show that with a good information system, the data and information provided will be more accurate and trustworthy, helping in making more appropriate decisions and improving the overall quality of education. It can be concluded that a well-integrated information system allows Islamic education institutions to improve operational efficiency, information accuracy, teaching quality, monitoring and evaluation, and stakeholder involvement. Implementation of information systems in Islamic education also plays a role in increasing transparency, accountability and information management based on Islamic values.